18F-fluorodeoxyglucose positron emission tomography immediately after chemoradiotherapy predicts prognosis in patients with locoregional postoperative recurrent esophageal cancer - Jingu, Keiichi; Kaneta, Tomohiro; Nemoto, Kenji; Takeda, Ken; Ogawa, Yoshihiro; Ariga, Hisanori; Koto, Masashi; Sakayauchi, Toru; Takai, Yoshihiro; Takahashi, Shoki; Yamada, Shogo (International journal of clinical oncology, 2010)
Objectives The objectives of this study were to reveal the utility of 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) within 7 days after chemoradiotherapy to predict prognosis in patients with postoperative recurrent esophageal cancer. Materials and methods Patients scheduled to undergo concurrent chemoradiotherapy for postoperative locoregional recurrence of esophageal cancer were recruited. Selection criteria were: (1) locoregional recurrence, (2) no previous radiation therapy, (3) planning treatment with concurrent chemoradiotherapy, (4) FDG-PET performed <2 weeks before chemoradiotherapy, and (5) no serious diabetes. FDG-PET was performed <7 days after chemoradiotherapy. No more treatment after chemoradiotherapy was given until disease progression was diagnosed according to the Response Evaluation Criteria in Solid Tumors (RECIST). Correlations of FDG-PET findings with cause-specific survival and local control rates were investigated prospectively. Results Twenty patients were enrolled. Median observation period of patients who survived was 45.0 months. Median maximum standardized uptake value (SUV max ) after chemoradiotherapy was 2.4, and median SUV max before chemoradiotherapy was 8.4. Cause-specific survival and local control rates were significantly better for patients with SUV max ≤ 2.4 after chemoradiotherapy (log-rank test, P = 0.033 and 0.010, respectively). SUV max before chemoradiotherapy tended to be correlated only with cause-specific survival rate (log-rank test, P = 0.076). Change in metabolic activity of FDG was significantly correlated with local control rate (log-rank test, P = 0.042). Conclusions FDG-PET performed even <7 days after chemoradiotherapy predicts prognosis in patients with postoperative recurrent esophageal cancer.